2019
DOI: 10.1142/s0217590819500553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Macroeconomic Stability on Financial Development in Developing Economies: Evidence From West African Region

Abstract: This paper examines the effects of macroeconomic stability on financial development in the West African region. Macroeconomic stability is measured based on five Maastricht Criteria’s variables namely inflation rate, real exchange rate, government debt, fiscal deficit and real interest rate. The study employs dynamic models on the panel data. We find that macroeconomic stability has significant effects on financial development in the region. Specifically, inflation rate, real exchange rate and fiscal deficit h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 66 publications
2
26
0
2
Order By: Relevance
“…Kim and Lin (2010) employed the PMG technique, and revealed that GDP accelerates financial development in 82 countries. Ibrahim and Sare (2018) used the dynamic GMM approach to reveal that GDP promotes financial development in 46 African countries, while Ehigiamusoe et al (2020) showed that GDP has a positive impact on financial development in 16 West African countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim and Lin (2010) employed the PMG technique, and revealed that GDP accelerates financial development in 82 countries. Ibrahim and Sare (2018) used the dynamic GMM approach to reveal that GDP promotes financial development in 46 African countries, while Ehigiamusoe et al (2020) showed that GDP has a positive impact on financial development in 16 West African countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kim and Lin (2010) reported that inflation has a long‐run negative effect on financial development, albeit the short‐run effect is positive in 87 countries. Bittencourt (2011) also examined the impact of inflation on financial development and reported that inflation has a detrimental effect on financial development in Brazil, while Ehigiamusoe et al (2020) showed that inflation has a negative impact on financial development in the West African region.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the aforementioned arguments, we argued that macroeconomic stability is essential for financial stability and market development. Using Maastricht Criteria and PMG estimations, Ehigiamusoe et al (2020) found a significant influence of macroeconomic stability on financial market development in West African countries. Similarly, utilizing two-step system GMM model, Abubakar and Kassim (2018) analyzed OIC countries while Aluko and Ibrahim (2020) selected sub-Saharan region to corroborate that financial institutions perform more effectively in the presence of stable macroeconomic environments such as more government expenditures, income, trade openness, financial openness, high institutional quality, and low inflation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the role of government transparency and anti-monopoly policy in promoting macroeconomic stability and financial market development, this study extends the related literature at the global level using a Panel ARDL-PMG approach. First, we estimate the underexplored effect of macroeconomic stability on financial market development using the sub-indexes of Global Competitive Index (GCI) as the evidence from disaggregate macroeconomic variables are largely mixed (Abubakar & Kassim, 2018;Aluko & Ibrahim, 2020;Ehigiamusoe, Lean, & Chan, 2020;Garcia & Liu, 1999). Macroeconomic stability fosters the financial development by reducing the vulnerability to the influence of external shocks (Vasylieva et al, 2018) and stimulating fairly constant output growth (Bourguignon, 2020).…”
Section: Introductionmentioning
confidence: 99%